Unveiling ovarian carcinosarcoma: a rare case report - Chadha, Saloni; Gupta, Sumedha; Kalwaniya, Dheer Singh; Dhir, Bhawuk (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian carcinosarcoma (OCS), also known as malignant mixed Müllerian tumor, is a rare and highly aggressive neoplasm, accounting for only 1-4% of all ovarian cancers. Characterised by both high-grade epithelial and mesenchymal components, it typically presents at an advanced stage, contributing to poor prognosis and low survival rates. A 36-year-old multiparous woman presented with progressive abdominal distention, pain, and gastrointestinal complaints. Her CA-125 levels were elevated (834 U/ml) and contrast-enhanced computed tomography (CT) findings revealed a large abdominopelvic mass. Histopathological examination confirmed OCS, with immunohistochemistry (IHC) showing positivity for pan-cytokeratin (PanCK) and S100, and negativity for WT1 on trucut biopsy. The patient received neoadjuvant chemotherapy with paclitaxel and carboplatin, followed by interval debulking surgery and adjuvant chemotherapy. Despite limited data on OCS, the case highlights the importance of cytoreductive surgery, optimal chemotherapy regimens, and emerging molecular-targeted therapies such as poly(ADP-ribose) polymerase (PARP) inhibitors and bevacizumab. Further research, including OCS-specific trials, is necessary to refine treatment approaches.